1996
DOI: 10.1111/j.1476-5381.1996.tb15638.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ovariectomy on depressed contractions to phenylephrine and KC1 and increased relaxation to acetylcholine in isolated aortic rings of female compared to male rabbits

Abstract: 1 Differences in vascular responses to phenylephrine, acetylcholine (ACh) and potassium chloride (KCl) were studied in rabbit aorta from female and male rabbits, in the absence and presence of an inhibitor of nitric oxide (NO) production, N0-nitro-L-arginine methyl ester (L-NAME, 100 yM).2 Phenylephrine and KCl-induced contractions, were significantly reduced in amplitude (P<0.01) in the rings from female rabbits compared to those from male rabbits. 3 ACh-induced relaxation was greater (P<0.01) in aortic rings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…More importantly, there is a more pronounced endotheliumdependent relaxation component of 17β-estradiol, which is particularly evident in female rats. This also has been seen in female rabbit aorta, in which it was suggested that tissues from female animals have higher capacity to release vasodilator substances compared with their male counterparts (Sanchez et al 1996). Our study actually reports that the overall magnitude in relaxation response in male endothelium-intact aorta did not significantly differ from that in the female endothelium-intact aorta.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…More importantly, there is a more pronounced endotheliumdependent relaxation component of 17β-estradiol, which is particularly evident in female rats. This also has been seen in female rabbit aorta, in which it was suggested that tissues from female animals have higher capacity to release vasodilator substances compared with their male counterparts (Sanchez et al 1996). Our study actually reports that the overall magnitude in relaxation response in male endothelium-intact aorta did not significantly differ from that in the female endothelium-intact aorta.…”
Section: Discussionsupporting
confidence: 80%
“…These experiments were conducted in the absence of both β-adrenoceptor blockade and inhibition of prostanoid synthesis, therefore it is likely that higher concentrations of noradrenaline could activate vasodilatory β-adrenoceptors and vasodilatory prostaglandin release. The differences between female and male endothelium-intact aortic response to noradrenaline relates to enhanced nitric oxide production in the female endothelium (Sanchez et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayashi et al . (1992) and Sánchez et al . (1996) both observed an enhanced basal and acetylcholine‐stimulated nitrite release from the aorta of female rabbits and rats compared to male controls, suggesting a greater release of NO.…”
Section: Introductionmentioning
confidence: 95%
“…However, it is clear from these latter studies that there exists sex differences in endothelium‐dependent regulation of vascular smooth muscle tone. Endothelium‐dependent vasorelaxation responses to acetylcholine in isolated aortae of the rat and rabbit have been demonstrated to be greater in the aortae from females compared to males (Hayashi et al ., 1992; Kauser & Rubanyi, 1993; 1994; Sánchez et al ., 1996). Hayashi et al .…”
Section: Introductionmentioning
confidence: 99%